Coasting Versus GnRH Antagonist Salvage for the Prevention of Ovarian Hyperstimulation Syndrome - Cavidan Gülerman; Nafiye Yılmaz; Ayla Sargın Oruç; Nazlı Özkan; Ayten Türkkanı; Esma Sarıkaya; Okan Yenicesu (Gynecology Obstetrics & Reproductive Medicine, 2013)
OBJECTIVE: The purpose of the present study is to compare the use of GnRH antagonist salvage versus coasting for the prevention of OHSS in patients undergoing IVF/ICSI cycles with long GnRH agonist protocol. STUDY DESIGN: Medical records of 91 patients (41 in coasting and 49 in GnRH antagonist group) identified as at high risk of developing OHSS were reviewed retrospectively. Groups were compared for occurrence of moderate and severe OHSS, serum estradiol on the day of HCG and IVF outcomes. RESULTS: There were no differences between the groups in terms of moderate and severe OHSS and clinical pregnancy rates. Serum estradiol levels were decreased significantly in GnRH antagonist group. Quality of the transferred embryos was better in the coasting group. CONCLUSION: Our results represent that both coasting and GnRH antagonist salvage are effective strategies to prevent OHSS in women undergoing long GnRH agonist IVF/ICSI cycles.